2022
DOI: 10.3390/met12030417
|View full text |Cite
|
Sign up to set email alerts
|

EIS Investigation of the Corrosion Behavior of Steel Bars Embedded into Modified Concretes with Eggshell Contents

Abstract: This investigation is focused on evaluation of the corrosion behavior of embedded steel bars (SB) into concretes. Conventional and modified concretes with eggshell are prepared. Although the effect of calcium carbonate on mechanical behavior is recognized and reported, their effects as eggshell (ES) particles replacing portions of sand and cement contents are reasonably scarce. Corrosion behavior is evaluated by electrochemical impedance spectroscopy (EIS) and the potentiodynamic polarization technique. Equiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 80 publications
(289 reference statements)
0
19
0
1
Order By: Relevance
“…Regarding the corrosion resistance of concretes with eggshell powder, according to generally accepted facts, concrete with ESP has a large loss in weight and strength when exposed to solutions of sulfates and chlorides [23,24]. For example, in [23], based on the results of experimental studies, it was found that the percentage of weight loss increases with the percentage of eggshell.…”
Section: Characteristics Of Concretes and Mortarsmentioning
confidence: 99%
“…Regarding the corrosion resistance of concretes with eggshell powder, according to generally accepted facts, concrete with ESP has a large loss in weight and strength when exposed to solutions of sulfates and chlorides [23,24]. For example, in [23], based on the results of experimental studies, it was found that the percentage of weight loss increases with the percentage of eggshell.…”
Section: Characteristics Of Concretes and Mortarsmentioning
confidence: 99%
“…In Figure 9 , is the environment impedance; Rct is the charge-transfer impedance; signifies the double-layer constant-phase element; refers to the adsorbed-layer impedance; is the adsorbed-layer constant-phase element. Because an equivalent circuit is used to determine the simulated values and for comparison with experimental data, a CNLS (complex nonlinear least squares) simulation was used, as previously reported [ 44 , 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…The reference electrode was a saturated calomel electrode (SCE). Electrochemical tests were started about 30 min after the working electrode was submerged in the solution in order to maintain the steady-state potential [ 44 , 63 , 64 ].…”
Section: Methodsmentioning
confidence: 99%
“…Em primeiro lugar, isso ajuda a determinar as reações que ocorrem em um sistema eletroquímico e selecionar um circuito elétrico a b c equivalente e avaliar seus os parâmetros. Estes contribuem para uma análise quantitativa e permitem a participação de cada elemento no mecanismo de corrosão ( Meyer et al, 2022).…”
Section: Resultsunclassified